2021
DOI: 10.1038/s41467-021-25174-6
|View full text |Cite
|
Sign up to set email alerts
|

Rational design of pyrrole derivatives with aggregation-induced phosphorescence characteristics for time-resolved and two-photon luminescence imaging

Abstract: Pure organic room-temperature phosphorescent (RTP) materials have been suggested to be promising bioimaging materials due to their good biocompatibility and long emission lifetime. Herein, we report a class of RTP materials. These materials are developed through the simple introduction of an aromatic carbonyl to a tetraphenylpyrrole molecule and also exhibit aggregation-induced emission (AIE) properties. These molecules show non-emission in solution and purely phosphorescent emission in the aggregated state, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
68
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 121 publications
(69 citation statements)
references
References 59 publications
1
68
0
Order By: Relevance
“…3B , the energy levels of the singlet and triplet excited states of the dimer are much denser than those of the monomer, which is beneficial for decreasing the energy gap between S 1 and T n . It has been reported that the ISC transitions could be realized within small energy gap (Δ E S1-Tn < 0.3 eV) between S 1 and T n 54 . Besides, only one orbital, either the occupied or the unoccupied, should be different in the relevant singlet and triplet states to ensure non-zero SOC integrals 55 .…”
Section: Resultsmentioning
confidence: 99%
“…3B , the energy levels of the singlet and triplet excited states of the dimer are much denser than those of the monomer, which is beneficial for decreasing the energy gap between S 1 and T n . It has been reported that the ISC transitions could be realized within small energy gap (Δ E S1-Tn < 0.3 eV) between S 1 and T n 54 . Besides, only one orbital, either the occupied or the unoccupied, should be different in the relevant singlet and triplet states to ensure non-zero SOC integrals 55 .…”
Section: Resultsmentioning
confidence: 99%
“…Time responsiveness is an appealing property in optics. [ 99–104 ] The emission color or intensity shows recognizable time‐dependent changes with other conditions remaining consistent. For example, phosphorescent materials always have time‐dependent emission decay after ceasing the excitation source.…”
Section: Time‐responsive 3d Codesmentioning
confidence: 91%
“…[9] Zhang et al reported tetraphenylpyrrole derivatives with two-photon excited phosphorescence, and nanoparticles were used for imaging. [10] Nevertheless, to the best of our knowledge, there is no report on the purely organic RTP system with both NIR emission and excitation in an aqueous environment, where it remains a formidable challenge at present.…”
Section: Introductionmentioning
confidence: 99%